2020
DOI: 10.1089/acu.2019.1369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electroacupuncture on Urea and Creatinine Levels in the Wistar Sepsis Model

Abstract: Objective: Sepsis is a life-threatening organ dysfunction caused by dysregulation of a host's response to infections. Sepsis-one of the most common contributing factors to acute kidney injuries in critically ill patients-is caused by bacterial endotoxins that lead to excessive production of proinflammatory cytokines. This condition can be treated with few side-effects by using electroacupuncture (EA) to regulate the neuroendocrine immune system to control the production of these cytokines. A number of studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In the Wistar sepsis model, EA reduced the levels of urea and creatinine in the blood, which are parameters of kidney function, and it showed that EA may prevent kidney injuries ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the Wistar sepsis model, EA reduced the levels of urea and creatinine in the blood, which are parameters of kidney function, and it showed that EA may prevent kidney injuries ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Its application improved survival rate in CLP model rats, and ameliorated cognitive impairment in rats with sepsis-related encephalopathy by inhibiting hippocampal synaptic damage, neuronal loss, oxidative stress, and release of inflammatory cytokines trough activation of the Nrf-2/HO-1 pathway and hippocampal α7 nicotinic acetylcholine receptors ( Han et al, 2018 ; Li C et al, 2020 ). In a rat model of sepsis, electroacupuncture pretreatment at ST36 attenuated inflammatory responses, decreased plasma urea, creatinine, and D-lactate levels, and increased intestinal tight junction protein occludin expression and intestinal barrier permeability, thereby reducing acute kidney and intestinal injury ( Zhu et al, 2015 ; Zhang Z et al, 2018 ; Harpin et al, 2020 ). In the rat CLP model, electroacupuncture treatment at ST 36 reduced the activity of plasma CK-MB and offered cardioprotection by reducing TNF-α, NO, MPO levels and water content in myocardial tissue by activating the cholinergic anti-inflammatory pathway ( Zhang L et al, 2018 ).…”
Section: Acupuncturementioning
confidence: 99%
“…EA has a significant inhibitory effect on oxidative stress and excessive inflammatory reactions in patients with SAKI. For example, Harpin et al found that EA pretreatment at the ST36 acupoint significantly reduced urea and creatinine levels in SAKI rat models and protected renal function (84). Endotoxic shock results in an abnormal adrenal glucose metabolism and decreased adrenal glycogen levels.…”
Section: Kidneymentioning
confidence: 99%